Case finding for chronic obstructive pulmonary disease: a model for optimising a targeted approach. Issue 6 (3rd June 2010) - Jordan, Rachel E; Lam, Kin-bong Hubert; Cheng, Kar Keung; Miller, Martin R; Marsh, Jennifer L; Ayres, Jon G; Fitzmaurice, David; Adab, Peymané
Abstract : Objectives: Case finding is proposed as an important component of the forthcoming English National Clinical Strategy for chronic obstructive pulmonary disease (COPD) because of accepted widespread underdiagnosis worldwide. However the best method of identification is not known. The extent of undiagnosed clinically significant COPD in England is described and the effectiveness of an active compared with an opportunistic approach to case finding is evaluated. Methods: A cross-sectional analysis was carried out using using Health Survey for England (HSE) 1995–1996 data supplemented with published literature. A model comparing an active approach (mailed questionnaires plus opportunistic identification) with an opportunistic-only approach of case finding among ever smokers aged 40–79 years was evaluated. There were 20 496 participants aged ≥30 years with valid lung function measurements. The main outcome measure was undiagnosed clinically significant COPD (any respiratory symptom with both forced expiratory volume in 1 s (FEV1 )/forced vital capacity (FVC) <0.7 and FEV1 <80% predicted). Results: 971 (4.7%) had clinically significant COPD, of whom 840 (86.5%) did not report a previous diagnosis. Undiagnosed cases were more likely to be female, and smoked less. 25.3% had severe disease (FEV1 <50% predicted), 38.5% Medical Research Council (MRC) grade 3 dyspnoea and 44.1% were current smokers. The active case-finding strategy can potentially identify 70% more new cases than opportunistic identification alone (3.8 vs 2.2 per 100 targeted). Treating these new cases could reduce hospitalisations by at least 3300 per year in England and deaths by 2885 over 3 years. Conclusions: There is important undiagnosed clinically significant COPD in the population, and the addition of a systematic case-finding approach may be more effective in identifying these cases. The cost-effectiveness of this approach needs to be tested empirically in a prospective study.